ANALISIS PERLAKUAN AKUNTANSI SYARIAH PADA PRODUK PEMBIAYAAN DI BMT BATIK MATARAM YOGYAKARTA - Mira Bela Sartika; Annisa Fithria (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2021)
This study aims to determine the accounting treatment of murabahah financing transactions, mudharabah financing, and musyarakah financing and to assess the suitability of accounting treatment for murabahah, mudharabah, and musyarakah financing with PSAK 102, PSAK 105, and PSAK 106 seen from the recognition, measurement, presentation, and disclosure. This research is qualitative research with a descriptive approach. The research object used is BMT Batik Mataram. The data collection techniques used are interviews and document review. The data analysis technique used is descriptive qualitative analysis, namely by analyzing the suitability of murabahah, mudharabah, and musyarakah financing transactions at BMT Batik Mataram with PSAK. Based on the study results, it is concluded that the accounting practices for murabahah, mudharabah and musyarakah financing transactions at BMT Batik Mataram are generally in accordance with PSAK 102, PSAK 105, and PSAK 106. However, BMT Batik Mataram is still not fully following PSAK No. 102 since it still imposes fines when there is a delay in instalments.